2015
DOI: 10.12973/eurasia.2015.1374a
|View full text |Cite
|
Sign up to set email alerts
|

Turkish Science Teachers’ Use of Educational Research and Resources

Abstract: Research results demonstrate that there is a gap between educational research and practice. Turkey is not an exception in this case. This study aims to examine to what extent and how educational research and resources are being followed, understood and used in classroom practices by science teachers in Turkey. A sample of 968 science teachers working at junior high schools in Eastern Anatolia region of Turkey was surveyed. The data were collected through a questionnaire consisting of multiple-choice and open-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…As a result, it was found that the most frequently used sources by pre-service science teachers in following and using the innovations in education are secondary resources (search engines such as google and yahoo). Similar findings were obtained from other studies in the literature carried out on teachers (Everton, 2002;Yavuz, 2009;Yıldırım et al, 2014;İlhan, Sözbilir, Şekerci, & Yıldırım, 2015).…”
Section: Conclusion and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As a result, it was found that the most frequently used sources by pre-service science teachers in following and using the innovations in education are secondary resources (search engines such as google and yahoo). Similar findings were obtained from other studies in the literature carried out on teachers (Everton, 2002;Yavuz, 2009;Yıldırım et al, 2014;İlhan, Sözbilir, Şekerci, & Yıldırım, 2015).…”
Section: Conclusion and Discussionsupporting
confidence: 91%
“…A large number of studies have been carried out on the self-efficacy beliefs of teachers and pre-service teachers recently; and in most of these studies the effect of some demographic characteristics (such as gender, the type of high school etc.) on self-efficacy were examined (Gercek et al, 2006;İlhan, Sözbilir, Şekerci, & Yıldırım, 2015;Kahraman, Yılmaz, Bayrak & Güneş, 2014;Ozdemir, 2008;Opera, 2008;Riggs, 1991;Saracaloglu & Yenice, 2009;Topkaya, 2016). In addition, there are other studies in which the relationship between the self-efficacy beliefs of pre-service teachers towards teaching science and attitude (Morgil et al, 2004), success and learning styles (Denizoglu, 2008) are examined.…”
Section: Introductionmentioning
confidence: 99%
“…When the general attitudes of the teachers are examined; teachers' attitudes towards educational researches are generally at a high level. In similar with the current study, there are studies which state that teachers have positive attitudes towards educational research [4], [23]. The teachers' attitudes towards educational research compared by the age groups in the current study and there were found statistically significant differences between the age groups.…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, it is essential to study the determinants of teachers' attitudes towards educational research. Although several studies are focusing on the attitudes of student teachers, teachers, and educators towards scientific research (Cousins & Walker, 2000;Korkmaz, Sahin, & Yesil, 2011;Papanastasiou, 2005;Walker, 2010), few studies focus on existing attitudes towards educational research (Everton et al, 2002;Ilhan et al, 2015a;Ilhan, Yilmaz, & Dede, 2015b;Ozturk, 2011). In these studies, teachers' attitudes towards educational research were mainly examined qualitatively (Dagenais et al, 2012;Ekiz, 2006;Shkedi, 1998;Vanderlinde & van Braak, 2010).…”
Section: Attitudes Towards Educational Researchmentioning
confidence: 99%
“…This is why information gained from scientific studies is invaluable. Many studies have concentrated on developing the qualities of teachers (e.g., Borko, Liston & Whitcomb, 2007;Ilhan, Sozbilir, Sekerci, & Yildirim, 2015a;Lin, Wang, Klecka, Odell, & Spalding, 2010). A growing number of studies also aimed to identify and develop primary and secondary school pupils (Sozbilir, Kutu & Yasar, 2012).…”
Section: Introduction 11 Theoretical Framework Of the Researchmentioning
confidence: 99%